The ethos of drama : rhetorical theory and dramatic worth - King, Robert L. (Robert Leo) (Book collections on Project MUSE., 2010)
Commenting in general on plays he has seen in performance, King applies ethical theory to the values of various dramatic techniques like costume, staging, action, and role playing. As an ultimate test of the theory, his concluding chapters study plays that respond to questions of overriding moral concern: the Holocaust, apartheid, and nuclear weaponry. --Book Jacket.